2017
DOI: 10.1016/j.jbankfin.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of prepayment penalties in mortgage loans

Abstract: We study the effect of mortgage prepayment penalties on borrowers' prepayments and delinquencies by exploiting a 2007 reform in Italy that reduced penalties on outstanding mortgages and banned penalties on newly-issued mortgages. Using a unique dataset of mortgages issued by a large Italian lender, we provide evidence that: 1) before the reform, mortgages issued to riskier borrowers included larger penalties; 2) higher prepayment penalties decreased borrowers' prepayments; and 3) higher prepayment penalties di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…LaCour-Little et al (2010), using the loan data from 2000 to 2006, showed that when the collateral value increases, the probability of prepayment of borrowers with liquidity restrictions increases. Beltratti et al (2017) investigated the effect of the policy of prepayment fees and found that the prepayment rate increases after the abolition of the prepayment fee. Steinbuks (2015) analyzed prepayment behavior before and after the ban on prepayment penalty in the US market and concluded that the prepayment is higher in the period after the ban than before.…”
Section: Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…LaCour-Little et al (2010), using the loan data from 2000 to 2006, showed that when the collateral value increases, the probability of prepayment of borrowers with liquidity restrictions increases. Beltratti et al (2017) investigated the effect of the policy of prepayment fees and found that the prepayment rate increases after the abolition of the prepayment fee. Steinbuks (2015) analyzed prepayment behavior before and after the ban on prepayment penalty in the US market and concluded that the prepayment is higher in the period after the ban than before.…”
Section: Determinantsmentioning
confidence: 99%
“…(2010), using the loan data from 2000 to 2006, showed that when the collateral value increases, the probability of prepayment of borrowers with liquidity restrictions increases. Beltratti et al. (2017) investigated the effect of the policy of prepayment fees and found that the prepayment rate increases after the abolition of the prepayment fee.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to the best of our knowledge, the empirical literature to date has neglected the effects of job protection on mortgage contract terms, for lack of household‐level administrative data matching information on mortgagors' employment conditions and the initial conditions of their mortgages. In addition, we contribute to the empirical banking literature on the determinants of households' mortgage conditions; related papers have investigated the role of financial regulation (Campbell, Ramadorai, and Ranish, 2015; Beltratti, Benetton, and Gavazza, 2017), market structure (Allen, Clark, and Houde, 2014; Benetton, 2021) and economic incentives for banks in their role of financial advisor (Foà et al ., 2019; Guiso et al ., 2022). Our focus is on the effect of job protection legislation.…”
Section: Introductionmentioning
confidence: 99%